2021
DOI: 10.1016/j.pedneo.2021.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Delivery management of suspected or confirmed COVID-19 positive mothers

Abstract: The Coronavirus Disease-2019 (COVID-19) pandemic has brought catastrophic impact on the world since the beginning of December 2019. Extra precautionary measures against COVID-19 during and after delivery are pivotal to ensure the safety of the baby and health care workers. Based on current literature, it is recommended that delivery decisions be discussed between obstetricians and neonatologists prior to delivery, and designated negative pressure delivery rooms should be arranged for COVID person under investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 37 publications
0
3
0
3
Order By: Relevance
“…15,16 DMIs that encourage cesarean section with its known risks to mothers, separate the delivery environment from the infant resuscitation environment, decrease motherinfant bonding by preventing skin-to-skin, and disrupt known benefits of delayed bathing in infants continue to be practiced without clear evidence of their effectiveness in preventing ENI and ND. 17 Sunuwar et al described a small retrospective review of 104 women who were SARS-CoV-2-positive during any trimester of pregnancy and delivered by vaginal delivery or cesarean section and followed their neonatal outcomes. 18 They found that in their infants 51% were born with low Apgar scores, 18% were born prematurely, 19% had low birth weight, 7% required neonatal intensive care unit admission, 3% experienced neonatal asphyxia, 2% died, and none were SARS-CoV-2-positive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 DMIs that encourage cesarean section with its known risks to mothers, separate the delivery environment from the infant resuscitation environment, decrease motherinfant bonding by preventing skin-to-skin, and disrupt known benefits of delayed bathing in infants continue to be practiced without clear evidence of their effectiveness in preventing ENI and ND. 17 Sunuwar et al described a small retrospective review of 104 women who were SARS-CoV-2-positive during any trimester of pregnancy and delivered by vaginal delivery or cesarean section and followed their neonatal outcomes. 18 They found that in their infants 51% were born with low Apgar scores, 18% were born prematurely, 19% had low birth weight, 7% required neonatal intensive care unit admission, 3% experienced neonatal asphyxia, 2% died, and none were SARS-CoV-2-positive.…”
Section: Discussionmentioning
confidence: 99%
“…Current reviews continue to combine discussions of DMI along with antepartum and postpartum care without evidence to direct DMI. 17,20 It is difficult to distinguish the risks of SARS-CoV-2 transmission attributable to antepartum care compared with postnatal delivery management. Between 1 and 15% of adults with COVID-19 have RNAaemia and pregnant women are more susceptible to COVID-19 than the general population.…”
Section: Discussionmentioning
confidence: 99%
“…(15) Obstetrik endikasyonlar dışında yapılan sezaryen doğumlarda maternal morbidite riski arttıran bir faktördür. (7) Sezaryen ile doğum, annenin klinik durumunda hızlı bozulma, akut organ yetmezliği, septik şok, gebe uterusa bağlı mekanik ventilasyonda zorluk ve fetal distres gelişmesi halinde uygun olacaktır. (15) Doğum şekline gebe bireysel olarak değerlendirildikten sonra karar verilir ve doğum izole odalarda uygun kişisel koruyucu ekipman giymiş ekip tarafından gerçekleştirilmesi gerekmektedir (11,13).…”
Section: Doğum şEkliunclassified
“…COVID-19 enfekte gebenin yanında refakatçi kalmasına izin verilmemelidir. (2,7,12) Bilindiği gibi doğum sırasında kadının, nabız, tansiyon, sıcaklık, oksijen satürasyonu gibi yaşamsal parametreleri her 3-4 saatte bir değerlendirilmesi gerekmektedir. Ayrıca SPO2 %94'ün altına düşerse arteryel kan gazı alınarak PaO2 bakılmalı, oksijen desteği sağlanmalıdır.…”
Section: İntrapartum Dönemunclassified
See 1 more Smart Citation